Linking Green Product, Process, and Finance Innovations to Firm Competitive Performance: Insights from Namanve Industrial Cluster, Uganda - Ahabyoona, Faith Mugisha; Mugisha, Henry; Lumu Emmanuel Roy, Muyingo; Bisaaso, Rita (INTI International University, 2025)
This study examined how green product, process, and finance innovations influence the competitive performance of manufacturing firms in Uganda’s Namanve Industrial Cluster. Guided by Porter’s Green Innovation Theory and Financial Innovation Theory, it argues that environmentally driven innovations enhance operational efficiency and competitiveness when supported by effective financial mechanisms. Using a cross-sectional survey design and quantitative approach, data were collected from 51 of 54 targeted firms (response rate = 94.4%). Correlation results showed significant positive associations between green product (r = .465**, p < .01), process (r = .546**, p < .01), and finance innovations (r = .749**, p < .01) with competitive performance. Hierarchical regression indicated that these variables jointly explained 67% of the performance variance, with green finance exerting the strongest predictive effect (β = .521, p < .01). The study concludes that green finance amplifies the performance impact of product and process innovations and recommends integrating circular economy practices and financial incentives to enhance sustainable competitiveness